Remarkable range extension of the previously monotypic braconid genus Wushenia Zettel (Hymenoptera: Braconidae: Cheloninae), with description of a second species from Australia - Kittel, Rebecca N.; Austin, Andrew D. (Zootaxa, 2013)
The apparently rare chelonine wasp genus Wushenia Zettel was previously known only from a single species Wushenia nana Zettel, collected by Townes at 1150 m from Wushe, Taiwan in 1983. Here we describe a second species, Wushenia australiensis sp. nov. from coastal New South Wales, Australia. This second species extends the known distribution of the genus from the Oriental into the Australasian region, indicating either an extreme disjunct distribution or that Wushenia may also occur on the landmasses inbetween, e.g. the Philippines, Malaysia, Indonesia and/or Papua New Guinea. In addition to a detailed description of the new species, a re-diagnosis of the genus and type species, and a key to species are presented.